(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Cancer disease is a leading global stress from the two decays, and the primary mode of treatment has not shown a promising curative approach because toxicity and drug resistance associated with conventional chemotherapy highlight the need for safer, effective alternatives. Citrullus colocynthis (bitter apple) is a medicinal plant reported to possess antioxidant, anti-inflammatory, and cytotoxic activities. This study investigated the anti-tumor potential of Citrullus colocynthis seed extract against Ehrlich Ascites Carcinoma (EAC)-induced solid tumors in mice. Solid tumors were established by s.c. injection of EAC cells (2 × 10⁶ cells/mouse) in experimental animals. Animals were treated orally with ethanolic seed extract of Citrullus colocynthis for 14 days. Tumor volume, body weight, hematological and biochemical parameters, antioxidant enzyme levels, and histopathological changes in tumor tissues were evaluated. Treatment with Citrullus colocynthis Substantial decrease tumor weight and volume (p < 0.001). Antioxidant enzymes were restored toward normal levels, and altered hematological parameters were significantly improved. Histopathological examination revealed reduced mitotic activity and extensive tumor necrosis, confirming inhibition of tumor progression. The ethanolic seed extract of Citrullus colocynthis could be used as an adjuvant therapy and can be considered along with the primary mode of treatment.